Measurement of electroweak production of a W boson in association with two jets in proton-proton collisions at root s=13 TeV - Sirunyan, A. M. (2020)
A measurement is presented of electroweak (EW) production of a W boson in association with two jets in proton-proton collisions at root s = 13 TeV. The data sample was recorded by the CMS Collaboration at the LHC and corresponds to an integrated luminosity of 35.9 fb(-1). The measurement is performed for the l nu jj final state (with l nu. indicating a lepton-neutrino pair, and j representing the quarks produced in the hard interaction) in a kinematic region defined by invariant mass m(jj) > 120 GeV and transverse momenta p(Tj) > 25 GeV. The cross section of the process is measured in the electron and muon channels yielding sigma(EW)(Wjj) = 6.23 +/- 0.12 (stat)+/- 0.61 (syst) pb per channel, in agreement with leading-order standard model predictions. The additional hadronic activity of events in a signal-enriched region is studied, and the measurements are compared with predictions. The final state is also used to perform a search for anomalous trilinear gauge couplings. Limits on anomalous trilinear gauge couplings associated with dimension-six operators are given in the framework of an effective field theory. The corresponding 95% confidence level intervals are -2.3 < c(WWW)/Lambda(2) < 2.5 TeV-2, -8.8 < cW/Lambda(2) < 16 TeV-2, and -45 < c(B)/Lambda(2) < 46 TeV-2. These results are combined with the CMS EW Z(jj) analysis, yielding the constraint on the cWWW coupling: -1.8 < c(WWW)/Lambda(2) < 2.0TeV(-2).